THE APPLICATION OF REGION BASED WARNING SYSTEM OF DENGUE HEMORRHAGIC FEVER SPREADING BY SMS GATEWAY WITH HAVERSINE METHOD FORMULA - Ni Luh Putu Ratih Indriyani (Universitas Pendidikan Ganesha, 2012)
This research was aimed to design the development and implementation asoftware of Region Based Warning System Of Dengue Hemorrhagic Fever SpreadingBy SMS Gateway With Haversine Method Formula. This research was expected tohelp the community in obtaining information related to the alert warning that the spreadof Dengue Hemorrhagic Fever in the area when the reporting of cases.This research was the development of an application was made to build a RegionBased Warning System Of Dengue Hemorrhagic Fever Spreading By SMS GatewayWith Haversine Method Formula, where the application will be able to accommodatethe data report of Dengue Hemorrhagic Fever, warning Dengue Hemorrhagic Feverdata, and user data that has been registered. The Development Of Region BasedWarning System As The Spread Of Dengue Hemorrhagic Fever SMS Gateway BasedBy Haversine Method Formula uses Waterfall model and was designed using the DataFlow Diagram (DFD).The Application Of Region Based Warning System Of Dengue HemorrhagicFever Spreading By SMS Gateway With Haversine Method Formula was implementedusing the programming language PHP and MySQL as the database as well asapplication to run Gammu SMS Gateway. After the testing process, it is concluded thatthe application provides the information Dengue Fever warning alert is sent via SMStext to take into account the coverage area according to the flight range of Aedesaegypti.